DARI ORGANISASI KE DUNIA PENDIDIKAN : MEMBANGUN SANTRI SEBAGAI PEMIMPIN DAN GURU MASA DEPAN DI PONDOK PESANTREN ASSIDIQIYAH 06 SERPONG - Anwar, Saiful; Utaminingsih, Sri; Febiyansyah, Febiyansyah; Pratiwi, Estherini Heratity; Ramadhan, Luky Fatur; Zulkifli, Zulkifli; Lailiah, Lailiah (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2025)
This community service program, titled "From Organization to Education: Building Santri as Future Leaders and Teachers," aims to develop leadership and organizational skills among the students (santri) of Pondok Pesantren Asshiddiqiyah 06 Serpong. The program, conducted through workshops and interactive sessions, is designed to equip santri with the essential skills required to become competent leaders and inspiring educators. The initiative highlights the important role of pesantren in shaping future leaders who integrate ethical leadership with modern educational practices. Through this program, participants are encouraged to enhance their leadership abilities while incorporating Islamic values, preparing them to lead and teach effectively in both personal and professional spheres. The program also focuses on fostering skills in communication, management, and decision-making, with an emphasis on real-world applications. Ultimately, the program aims to build a strong foundation for santri to become change-makers in their communities.